2018
DOI: 10.1002/pi.5533
|View full text |Cite
|
Sign up to set email alerts
|

Rheo‐Raman spectroscopic study of microscopic deformation behavior for ultra‐low‐density polyethylene

Abstract: In situ Raman spectroscopy was applied to ultra-low-density polyethylene (ULDPE) to investigate the microscopic deformation behavior under uniaxial stretching. It was found that the crystalline chains of ULDPE show a bimodal molecular orientation parallel and perpendicular to the stretching direction beyond the elastic region. The peak shifts of C − C stretching modes of the crystalline chains obviously depend on the polarization direction, suggesting that the microscopic load sharing is anisotropic. Whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…These changes in the mechanical properties are attributed to the polymer topology which could influence complex factors such as entanglement, crystallinity, and morphology. [13][14][15] Among branched polymers, comb polymers have recently attracted attention for helping the understanding of the mechanical and rheological properties of the branched topology by the quantification of the molecular structure defined by the backbone length, side chain length, and grafting density. 1,15,16 The unified scaling model beyond the chemical structure can describe the rheological properties, such as the entanglement plateau modulus, 15,17 zero shear viscosity, 18 strain hardening factor, 18 and relaxation time, allowing the prediction of mechanical properties 19 in soft materials.…”
Section: Introductionmentioning
confidence: 99%
“…These changes in the mechanical properties are attributed to the polymer topology which could influence complex factors such as entanglement, crystallinity, and morphology. [13][14][15] Among branched polymers, comb polymers have recently attracted attention for helping the understanding of the mechanical and rheological properties of the branched topology by the quantification of the molecular structure defined by the backbone length, side chain length, and grafting density. 1,15,16 The unified scaling model beyond the chemical structure can describe the rheological properties, such as the entanglement plateau modulus, 15,17 zero shear viscosity, 18 strain hardening factor, 18 and relaxation time, allowing the prediction of mechanical properties 19 in soft materials.…”
Section: Introductionmentioning
confidence: 99%
“…For high-density PE (HDPE) with a crystallinity of more than 60 vol%, the values of 〈P 2 〉 and 〈P 4 〉 during the yield deformation are in the region (iv): the values of 〈P 4 〉 decrease in the yield region, whereas 〈P 2 〉 increases monotonously with increasing strain. This result suggests that the crystalline chains orient to the oblique direction (θ = 30-50°) even during uniaxial stretching [38][39][40][41] . Oblique orientation of the crystalline chains has been observed in both PE and PP 43) , and is caused by the suppression of the molecular orientation due to the excluded volume effect of the rigid and bulky lamellar structure 44) .…”
Section: Molecular Orientationmentioning
confidence: 85%
“…The crystalline chains orient markedly to the stretching direction beyond the yield point, whereas the orientation function of the amorphous chains immediately increases in the elastic region and reaches an asymptotic value in the strain-hardening region 37) . Kida et al measured the strain dependences of both orientation parameters and the orientation distribution function of crystalline chains during the uniaxial elongation of various PE samples [38][39][40][41] at various temperatures 42) . For high-density PE (HDPE) with a crystallinity of more than 60 vol%, the values of 〈P 2 〉 and 〈P 4 〉 during the yield deformation are in the region (iv): the values of 〈P 4 〉 decrease in the yield region, whereas 〈P 2 〉 increases monotonously with increasing strain.…”
Section: Molecular Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Takumitsu Kida et al . highlight in situ Raman spectroscopy study of ultra‐low‐density polyethylene (ULDPE) and investigated the microscopic deformation behavior under uniaxial stretching . They found that the crystalline chains of ULDPE showed a bimodal molecular orientation parallel and perpendicular to the stretching direction beyond the elastic region.…”
mentioning
confidence: 99%